Weed control efficacy and short term weed dynamic impact of three nonselective herbicides in immature oil palm plantation. - Mohamad, Rosli; Juraimi, Abdul Shukor; Omar, Dzolkhifli; Wibawa, Wahyu; Mohayidin, Mohd Ghazali; Begum, Mahfuza (Friends Science Publishers, 2009)
Efficacy of three herbicides (paraquat, glufosinate ammonium & glyphosate) in immature oil palm plantation was evaluated. The experiment was quadruplicated in randomized complete block design with 13 treatments viz. paraquat at 200, 400, 600,800 g a.i. ha-1, glufosinate ammonium at 200, 400, 600, 800 g a.i. ha-1 and glyphosate at 400, 800, 1200, 1600 g a.i. ha-1 and an untreated check as control. Glufosinate ammonium and glyphosate were much better than paraquat as supported by data onweed mortality, weed dry weight, weed density and sum dominance ratio (SDR). Glufosinate ammonium and glyphosate also affected short-term weed dynamic and were found to be more suitable to control mixed weed in immature oil palm plantation.